Comparative Seismology Of The Witwatersrand Basin And Bushveld Complex And Emerging Technologies To Manage The Risk Of Rockbursting - R. J. Durrheim (The Southern African Institute of Mining and Metallurgy, 2005)
The seismicity of the Witwatersrand Basin and Bushveld Complex has been analysed, revealing significant differences in source and damage mechanisms. A comparison of mining taking place at similar depths and extraction ratios indicates that the seismic energy release rate is considerably lower in the Bushveld Complex. Technologies introduced in the past decade to manage the risk of rockbursting are reviewed and assessed. These include geophysical methods to detect hazardous structures ahead of mining, new mining layouts and support systems, and the mechanization of in-stope processes. Despite important differences in geology, in situ stress, mining layouts and methods, there are many opportunities for the reciprocal transfer of knowledge, experience and technology between the gold and platinum mining sectors to improve the management of the rockburst risk.